Posterior shoulder instability in a professional basketball player: A level 3 CASE report - Anumba, M. C.; Citriniti, A.; Decker-Hamm, M. (Journal of Athletic Training, 2019)
Background: Posterior shoulder instability accounts for about 5% of all shoulder instability. Imaging has confi rmed that 86% of cases are found to have a Reverse HillSachs lesion accompanying posterior instability. Course of treatment, either surgical or conservative, depends on the size of the bony lesion; however, surgery is most often recommended as the fi rst treatment option. Conservative treatment has been used with a stable glenohumeral joint and a defect of less than 25% of the articular surface. Conservative treatment can have positive results, as seen in this Level 3 CASE Study, but 65% to 80% of cases show recurrent posterior dislocation. Patient: A 26yearold professional, right hand dominant male basketball player, with a previous history of two left shoulder subluxations, presents with left shoulder pain during a basketball game. The injury occurred as the athlete reached for a loose ball and collided into another player, resulting in a pop sensation in his shoulder. The athlete was evaluated by the team athletic trainer (ATC) and team physician. Common fi ndings from both evaluations were painful and decreased external and internal rotation strength and decreased range of motion (ROM) with abduction and fl exion of the left shoulder. The following special tests provided a positive response: Kim test, Jerk test, and Sulcus sign. After the exam, the physician requested an Xray and MRI with contrast. The results revealed a left posterior shoulder subluxation, Reverse HillSachs lesion, and humeral avulsion of the posterior band of the inferior glenohumeral ligament. The team surgeon recommended surgery, however the athlete decided to obtain two other opinions, of which one recommended surgery and the other recommended conservative treatment. Intervention or Treatment: The athlete decided to rehabilitate his shoulder in an effort to return with enough time to complete the season. The athlete was immobilized for one week postinjury and rehabilitation in the following weeks focused on ROM, strengthening of shoulder stabilizers, and cardiovascular conditioning. During week 4, the athlete began noncontact practice, followed by a week of light contact practice. Full contact practice began at week 6 and the athlete returned to play at week 7. According to the literature, rehabilitation should focus on restoration of scapulothoracic and glenohumeral kinematics, control, and function. The athlete's rehabilitation was in line with the recommendations for conservative treatment of posterior shoulder instability, which is to restore shoulder stability. Outcomes or Other Comparisons:There lacks evidence about the most appropriate conservative treatment for posterior shoulder instability. The general consensus from the literature states that 6 months of rehabilitation can be benefi cial; however, the athlete in this case safely returned after 7 weeks of intensive rehabilitation. Conclusions: Posterior shoulder instability is rare in the athletic population, other than in football players during blocking, and the most common treatment is surgical intervention. According to the literature and the shoulder specialist, the desired course of treatment should have been an open repair in order to visualize the full extent of shoulder damage. This case report presents a professional basketball player with posterior shoulder instability who chose conservative rehabilitation in order to complete his basketball season. Clinical Bottom Line: From a rehabilitation perspective, the consensus for success with conservative treatment is based on size of bony lesion and overall ability to maintain shoulder stability. However, other than those recommendations, there is no clear protocol for conservative management of posterior shoulder instability. This case highlights the possibility of such nonsurgical management based off impairments and presentation. Further investigation into the most effective conservative approach and time to return to play is needed.